Microstructure, mechanical properties and fracture behaviors of large-scale sand-cast Mg-3Y-2Gd-1Nd-0.4Zr alloy - Lixiang Yang; Yuanding Huang; Zhengquan Hou; Lv Xiao; Yuling Xu; Xiwang Dong; Fei Li; Gerrit Kurz; Baode Sun; Zhongquan Li; Norbert Hort (Journal of Magnesium and Alloys, 2023)
In order to improve the ductility of commercial WE43 alloy and reduce its cost, a Mg-3Y-2Gd-1Nd-0.4Zr alloy with a low amount of rare earths was developed and prepared by sand casting with a differential pressure casting system. Its microstructure, mechanical properties and fracture behaviors in the as-cast, solution-treated and as-aged states were evaluated. It is found that the aged alloy exhibited excellent comprehensive mechanical properties owing to the fine dense plate-shaped β' precipitates formed on prismatic habits during aging at 200 °C for 192 hrs after solution-treated at 500 °C for 24 hrs. Its ultimate tensile strength, yield strength, and elongation at ambient temperature reach to 319 ± 10 MPa, 202 ± 2 MPa and 8.7 ± 0.3% as well as 230 ± 4 MPa, 155 ± 1 MPa and 16.0 ± 0.5% at 250 °C. The fracture mode of as-aged alloy was transferred from cleavage at room temperature to quasi-cleavage and ductile fracture at the test temperature 300 °C. The properties of large-scale components fabricated using the developed Mg-3Y-2Gd-1Nd-0.4Zr alloy are better than those of commercial WE43 alloy, suggesting that the new developed alloy is a good candidate to fabricate the large complex thin-walled components.